PENERAPAN SISTEM PERADILAN TERHADAP ANAK PELAKU PENGULANGAN PIDANA KASUS PEMBUNUHAN BERENCANA MENURUT SISTEM PERADILAN PIDANA ANAK BERDASARKAN UNDANG-UNDANG NOMOR 11 TAHUN 2012 - Pamungkas Djati, Maheswara; Gultom, Potler (MALA IN SE: Jurnal Hukum Pidana, Kriminologi, dan Viktimologi, 2025)
This research aims to analyze how the juvenile justice system is applied to children involved in recidivist crimes, particularly in premeditated murder cases, with reference to the provisions of the Juvenile Justice System Act No. 11 of 2012. The research method used is a case study, focusing on Court Decision No. 3/Pid.Sus-Anak/2022/PN Buntok. Data was collected through the analysis of court decisions and interviews with legal practitioners and related parties. This study examines the application of the juvenile justice system in the context of premeditated murder cases involving repeat juvenile offenders and evaluates how well the law is implemented in judicial practice.The results indicate that the application of the juvenile justice system in recidivist cases, especially in premeditated murder, faces significant challenges in balancing the protection of the child's rights with societal justice. Law enforcement needs to be more sensitive to the rehabilitation needs of juveniles and prevention of recidivism through a more integrated approach and greater attention to the underlying factors driving the child's behavior.